2014
DOI: 10.1016/j.ijchv.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Long QT syndrome, cardiovascular anomaly and findings in ECG-guided genetic testing

Abstract: Objective: Patients with inherited long QT syndrome (LQTS) are prone to torsade de pointes and sudden death (SD). Identifying affected individuals is important for SD prevention. This study aimed to determine the cause and genotype-phenotype characteristics of LQTS in a large Omani family. Methods: Upon LQTS diagnosis of a 5-year-old girl (proband), targeted mutation screening was performed based on the gene-specific ECG pattern identified in her mother. ECG-guided family genotyping was conducted for identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…In recent years, with the emerging technology of next-generation sequencing, there is a tendency to perform genome-wide gene hunting in LQTS, which, in turn, further boosts the cost of genotyping. In our study, 92% (172/186) of LQTS patients with genotype-positive results were single-gene mutation carriers [20] of KCNQ1 , KCNH2 and SCN5A . This indicates that screening rare genes or conducting genome-wide screening is perhaps unnecessary in most cases.…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, with the emerging technology of next-generation sequencing, there is a tendency to perform genome-wide gene hunting in LQTS, which, in turn, further boosts the cost of genotyping. In our study, 92% (172/186) of LQTS patients with genotype-positive results were single-gene mutation carriers [20] of KCNQ1 , KCNH2 and SCN5A . This indicates that screening rare genes or conducting genome-wide screening is perhaps unnecessary in most cases.…”
Section: Discussionmentioning
confidence: 81%
“…However, we were unable to make a definitive diagnosis because a QT prolongation was not proven. Through systematic literature review, we identified several additional cases of KCNH2 mutation with LVNC-LQTS combined phenotype (AlSenaidi et al, 2014;Ogawa et al, 2009;Rammes et al, 2017). The first association between LVNC and KCNH2 mutations was described by Ogawa et al (2009) reporting 2 unrelated individuals with isolated LVNC and LQTS carrying missense mutations in KCNH2.…”
Section: Discussionmentioning
confidence: 99%
“…The first association between LVNC and KCNH2 mutations was described by Ogawa et al (2009 ) reporting 2 unrelated individuals with isolated LVNC and LQTS carrying missense mutations in KCNH2. Subsequent AlSenaidi et al (2014 ) reported a 5-year-old girl of consanguineous Oman parents carrying a KCNH2 homozygous frameshift mutation in association with phenotypes including LVNC, dilated ascending aorta and LQTS. Interestingly, both the parents of the girl carried this KCNH2 heterozygous mutation but neither presented with LVNC, indicating that LVNC is incomplete in LQTS patients with KCNH2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic heterogeneity in long QT 3 and Brugada syndromes 4 has made this new genetic testing approach mandatory. The advantages of NGS versus the SSM in cases of genetic heterogeneity are undeniable, but NGS is still expensive and unaffordable for developing countries.…”
Section: Next-generation Sequencing: Available For Everyone?mentioning
confidence: 99%